Technology-Based Learning Innovation in Community Service: Impact on Improving Education Access in Remote Areas - Wajnah, Wajnah; Kusmawan, Udan; Arifin, Syaadiah; Muhammadiyah, Mas'ud; Arsyad, Muhammad (Universitas Pahlawan Tuanku Tambusai, 2025)
This study examines the impact of technology-based learning innovations in community service programs aimed at improving education access in disadvantaged areas. Using a qualitative research approach, data were collected from educational practitioners, community leaders, and policymakers through in-depth interviews and document analysis. The findings reveal that digital learning tools, online platforms, and mobile-based education programs significantly enhance learning opportunities for marginalized communities. However, challenges such as digital literacy, infrastructure limitations, and funding remain substantial. The study underscores the necessity of a collaborative approach between governments, NGOs, and technology providers to ensure sustainable educational development.